2013
DOI: 10.1080/19392699.2012.717566
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Using Table Type Air Separators for Coal Cleaning

Abstract: In the present study, the application of table type air separators was investigated on three lignite samples and a hard coal sample collected from several regions in Turkey. The Yenikoy lignite sample was used to determine optimum test conditions. These test conditions were used to study Soma, Corum lignite, and Zonguldak hard coal samples with reference to feed rate, riffle height, table frequency, and table slope. Results were analyzed to determine calorific values and ash contents of clean coal and tailing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The exception is that dry cleaning may be suitable for the upgrading of 3-1 mm size fraction Hüsamlar coal. Besides, the separation performance of three Turkish lignite samples using table-type air separator was investigated, which indicated that the table-type air separator could be used for effective separation of Turkish lignite [60]. Air dense medium fluidized bed is another dry density-based separator [61][62][63].…”
Section: Dry Methodsmentioning
confidence: 99%
“…The exception is that dry cleaning may be suitable for the upgrading of 3-1 mm size fraction Hüsamlar coal. Besides, the separation performance of three Turkish lignite samples using table-type air separator was investigated, which indicated that the table-type air separator could be used for effective separation of Turkish lignite [60]. Air dense medium fluidized bed is another dry density-based separator [61][62][63].…”
Section: Dry Methodsmentioning
confidence: 99%
“…Currently, Fuhe Ganfa Xuan mei (FGX) separator is the most well-known separator with high efficiency for coal separation in China [ 246 , 247 ]. The FGX separator consists of a perforated inclined deck with several air chambers (usually three), a vibrating device, a drive and a mechanism which allows the change of table inclination angle.…”
Section: Dry-type Gravity Separation Technologiesmentioning
confidence: 99%
“…While heavier particles gravitate through the bed and come in contact with the deck surface and move in the direction of the outlet of rock, is discharged by the baffle plate that directs them to the discharge chute of rock [ 175 , [248] , [249] , [250] ]. Particle size [ [250] , [251] , [252] , [253] ], feed rate [ 246 ], air flow rate [ 249 , 256 ], table transverse inclination [ 246 , 256 ], table longitudinal inclination [ 246 , 256 ], table vibration frequency [ 246 ], riffle height [ 246 ], and partition plate height [ 248 , [257] , [258] , [259] ] are the parameters that could affect the separation efficiency of both conventional air table and FGX separator (Table S4). FGX separator could also be applied to remove heavy metals like mercury from hard coal [ 254 ] and used for low-rank lignite beneficiation with the combination of subsequent infrared (IR) drying [ 250 ].…”
Section: Dry-type Gravity Separation Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…China is the world's largest producer and consumer of coal [3,4]. Coal bene ciation is applied to remove minerals that decrease the value of the coal product, such as carbonate, pyrite, and silicate [5,6]. Coal beneciation is a key process for deep processing of raw coal, and it is also the source technology for clean and e cient utilization of coal and the basis for purifying air pollution [7,8].…”
Section: Introductionmentioning
confidence: 99%